Anti-Muslim campaign in Sri Lanka and responses of the Buddhists - Razick, Ahamed Sarjoon; Khaidzir Hj Ismail; Ahmad Suanawari Long; Kamarudin Salleh (Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2016)
Sri Lanka is a country where multi ethnic, multi language, multi religious people live. Buddhist is the predominant religious group in Sri Lanka, while the Muslims formed second biggest religious group, next to Tamils. The Buddhist-Muslim relationship has been prevailing and everlastingly for centuries, sbut for a couple of years, a disturbing trend has wide spread, between them. This conflictual nature has come to appear aftermath of the anti-Muslim campaign by few Buddhist Nationalist Groups (BNGs) in Sri Lanka. The basic purpose of the anti-Muslim campaign in Sri Lanka is to propagate bad image of Islam and the Muslims of Sri Lanka, to create a negative perspective among Buddhist public about Islam and Muslims and to distort the good relationship of Buddhists and Muslims in Sri Lanka. In recent past years, few Buddhist Nationalist Groups, campaigned against Halal certification on consumer goods, Hijab of Muslim women, cattle slaughtering, worship places and prayer services in Sri Lanka. Furthermore, they have spread out the idea, that the latest Muslim developments within the country; especially in terms of religion; is a notable threat to Buddhism and to the Buddhist people. These wrong perceptions, ideas and point of views are major factors in Muslim-Buddhist bad relationship, in recent past years. This research attempts to analyze the point of views of few Buddhists, on recent campaigns, against the Muslims, undertaken by the BNGs, in recent past years, by conducting a semi structured interviews in 14 selected Buddhist majority districts of Sri Lanka. Based on the results, it is clearly affirmed that, the recent anti-Muslim campaign, by the BNGs, have created a suspicious nature Muslim stereotype among a group of Buddhists in the society, over a fact that a Buddhist-Muslim relationship in recent past years has damaged a lot. However, these campaigns have not changed the whole Buddhist’s mood and point of views, in terms of maintaining a good relationship with Muslims in Sri Lanka, without any break, as the majority know and respect Muslim citizens of Sri Lanka, because of the behavior and support of Muslims towards the Sri Lankan state, during the civil war (1984-2009) and pre-war time in Sri Lanka.